2006
DOI: 10.1017/s1355617706060255
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative analyses of clock drawing in frontotemporal dementia and Alzheimer's disease

Abstract: The clock drawing test (CDT) is a widely used cognitive screening test. It is useful in identifying focal lesions and cognitive deficits in dementia groups. Lately, several studies attempted its use to differentiate between dementia subtypes. Although many studies have examined the CDT in dementia populations, research into the use of clock drawing in frontotemporal dementia (FTD) is limited. We examined quantitative (global) and qualitative (specific error type) differences on the CDT between FTD (n = 36) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 43 publications
2
50
1
Order By: Relevance
“…For instance, in a sample of autopsy-verified FTD patients, Rascovsky et al [131] observed similar scores in copying geometrical figures, but higher overall CDT scores in FTD compared to AD patients. In the same vein, Blair et al [132] reported higher overall scores, and fewer conceptual, spatial, and planning errors in FTD compared to the AD group (see Fig. 1).…”
Section: Drawing Disorders In Frontotemporal Dementiamentioning
confidence: 73%
See 1 more Smart Citation
“…For instance, in a sample of autopsy-verified FTD patients, Rascovsky et al [131] observed similar scores in copying geometrical figures, but higher overall CDT scores in FTD compared to AD patients. In the same vein, Blair et al [132] reported higher overall scores, and fewer conceptual, spatial, and planning errors in FTD compared to the AD group (see Fig. 1).…”
Section: Drawing Disorders In Frontotemporal Dementiamentioning
confidence: 73%
“…Instead, in a study on a sample of outpatients matched for general cognitive impairment VaD scored significantly lower than AD on CDT, likely related to poorer executive abilities in VaD patients [124]. Kitabayashi et al [125] stratified their patient sample by general cognitive impairment, and found [125] CDT Conceptual and spatial/planning errors in AD in all disease stages; conceptual and graphic errors in moderate-severe VaD Fukui [126] CDT, figure copying No difference at mild disease stages; sVaD worse than AD on both tasks at severe stages Graham [127] ROCF No difference between AD and sVaD Comparison AD-FTD Rascovsky [131] CDT, figure copying AD worse than FTD on overall CDT score; no differences in figure copying Blair [132] CDT AD worse than FTD; less conceptual, spatial and planning errors in FTD than in AD Razani [133] CDT AD worse than right-and left-onset FTD Thompson [134] Figure copying AD worse than FTD; less spatial errors, but more perseverations in FTD than in AD Possin [135] Simplified ROCF AD worse than FTD Perri [136] ROCF AD worse than FTD Gorno-Tempini [137] ROCF AD worse than non fluent PA Grossi [138] ROCF No difference between AD and bvFTD Gasparini [139] ROCF No overall difference between AD and bvFTD; AD better than bvFTD in drawing details Rascovsky [141] Figure copying…”
Section: Drawing Disorders In Vascular Dementiamentioning
confidence: 99%
“…In this sense, the degraded semantic knowledge, assessed by naming tests, may impair CDT performance. Other authors 31 , wor king with AD and frontotemporal dementia patients (including semantic dementia), found quantitative and qualitative impairments in CDT performance that may, at least partial ly, be related to semantic deficits. Functional neuroimaging studies with AD patients identified posterior left temporal lobe (areas related to language and semantic processing) blood flow to be a predictor of CDT performance 32,33 .…”
Section: Discussionmentioning
confidence: 92%
“…In stark contrast, clock scoring within the field of neuropsychology employs an analysis of errors, for error type (e.g. semantic, graphomotor, perseverative) informs clinicians about lesions/pathology [3,10,11,17]. Cosentino et al [10] provide one error analysis approach based on cognitive theory and common dementia pathology.…”
Section: Introductionmentioning
confidence: 99%